A renewable energy system for asynchronous motor with speed control - Chen, Junyan (2014)
It is quite necessary to build a self-sufficient energy system in the remote region deep down in the desert or an island far in the ocean, because of the high cost of transferring electricity. A very simple system is introduced in this dissertation which comprises of a converter, an inverter and a motor speed control with the premise of a stable MPPT. The converter part is made up of a fundamental booster-converter with the usage to boost the voltage from low to high. Boost-converter is not the only converter which can realize the function, but also a lot of other converters can do it; however, for the sake of simplicity and the convenience for understanding, the basic converter, boost-converter, is chosen in this dissertation. The inverter is a bit more complicated than the converter, for it needs to be three-phase. In this dissertation, two kinds of control methods, PR control strategy and SVPWM strategy, are investigated. These twn o methods are the advanced technologies in modem world, although complicated and costly, however more efficient than the traditional controlling method like SPWM. Motor occupies a large part of modem industry work; almost all the production associate with the motor more or less. In this dissertation, the motor speed control is investigated by using PR controlling method; three different frequencies are applied to the motor in order to achieve different mechanical speed. After simulation by using MATLAB/Simulink, the finally results are presented in chapter 5. It can be clearly seen that the speed varies as the frequency changes.